ANALISIS PENGARUH EKSPOR, JUMLAH PENDUDUK, DAN INVESTASI TERHADAP PERTUMBUHAN EKONOMI DI INDONESIA - Arnifa Fitria Nurrahmayanti Wibowo (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2023)
One of the economic indicators that can be used as a benchmark for people's welfare in a country is economic growth. Economic growth can be defined as an increase in demand for products and services, the results of which will lead to an increase in national income. This study aims to determine the effect of exports, population, and foreign direct investment on economic growth in Indonesia in 1990-2019. This analysis uses the Vector Error Correction Model (VECM) method because there is cointegration in the VAR test. In this research, the data source used is secondary data. The results of the analysis show that the export and FDI variables have a significant long-term effect on economic growth, while the population variable has no long-term effect on economic growth.